Production Of Protein Hydrolysates From Soy Okara By Aspergillus Oryzae - Sulaiman, Wan Nurnadia Diyana (Universiti Sains Malaysia, 2020)
Soy okara is the soybean pulp or soybean curd residues that obtain after undergoing water-extractable fraction process used to produce bean curd or soymilk. In soy industry, the amount of soy okara produced every day is higher than expected which in high protein content. It can increase the environmental pollutions cause of highly susceptible to putrefaction in fresh okara. Okara protein hydrolysate is prepare by cultivation with Aspergillus oryzae to produce functional protein for foods and animal feeds. In this research, okara will be cultivated with different percentage of A. oryzae inoculum at 25°C incubation for 72 hours.